A low-temperature sintered high-magnetic-permeability high-Curie-temperature NiCuZn material and preparation method thereof
By preparing a low temperature sintering high magnetic guidance rate, the temperature Nicuzn material is high, and the main components and side components of a specific ratio are used, and through the heat pressure sintering process, it solves the problem that the existing materials are difficult to achieve a number of excellent performance at the same time. Economic magnetic materials are prepared to meet the development needs of electronic products.
Patent Information
- Application Number
- CN202410256050.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-06
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-03-06
AI Technical Summary
The existing NiCuZn soft ferrite materials are difficult to achieve high initial permeability, high Curie temperature, high saturation flux density and high surface resistance at the same time, and cannot meet the needs of micro high-quality inductors, pulse transformers, electromagnetic interference suppressors, etc. , it does not conform to the development trend of miniaturization, high power and wide temperature.
By preparing a low-temperature sintering and high magnetic guidance rate, the temperature Nicuzn material is used, and 49.0-54mol % FE2O3, 22.5-36.5mol % Zno, 12.5-19.0mol % NIO and 2.0-4.5mol % CUO are used as the main ingredient, adding V2O5, adding V2O5, MOO3, ZRO2, and WO3 are used as deputy scores. The sintering temperature and time are controlled by the heat pressure sintering process to improve the density and uniformity of the material.
The high initial magnetic guidance rate, Curie temperature, saturated magnetic flux density and surface resistance of Nicuzn materials are realized, and the requirements for miniaturization and high working temperature on magnetic materials are simplified, and the preparation process is simplified, reducing costs and energy consumption.
Smart Images

Figure GDA0005175306520000051 
Figure GDA0005175306520000061 
Figure GDA0005175306520000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of soft ferrite materials, and in particular to a low-temperature sintered high-permeability high-Curie temperature NiCuZn material and a preparation method thereof. Background Art
[0002] NiCuZn soft ferrite materials have the advantages of high resistivity ρ, high cut-off frequency, high initial magnetic permeability μi, low loss, low temperature coefficient, etc., and can be widely used in high-frequency inductor cores, near field communication (NFC) systems, multilayer chip inductors (MLCI) and anti-EMI devices. The initial magnetic permeability of existing NiCuZn soft ferrite materials is mostly lower than 1600, and the higher the magnetic permeability of NiCuZn soft ferrite materials, the lower the Curie temperature (Tc). For example, the Tc of NiZn series materials with initial magnetic permeability greater than 1500 and room temperature saturation magnetic flux density greater than 250mT is about 100℃, and the magnetic permeability of NiZn series materials with higher Tc is usually less than 1000. Low Tc means that the operating temperature range of the material is narrower, which limits its application in many fields. In the existing public technical documents and patent documents, some have low initial magnetic permeability, some have low Curie temperature, and some have low saturation magnetic flux density. It is difficult to achieve high initial magnetic permeability, high Curie temperature, high saturation magnetic flux density and high surface resistance at the same time. These problems make it impossible to meet the use requirements of soft magnetic materials for miniature high-quality inductors, pulse transformers, electromagnetic interference suppressors, etc., and do not conform to the development trend of miniaturization, high power and wide temperature of electronic products. Summary of the invention
[0003] In order to solve at least one of the above technical problems, a soft magnetic ferrite material with high initial magnetic permeability, high Curie temperature, high saturation magnetic flux density and high surface resistance is developed. The present application provides a low-temperature sintered high magnetic permeability and high Curie temperature NiCuZn material and a preparation method.
[0004] On the one hand, the present application provides a low-temperature sintered high magnetic permeability and high Curie temperature NiCuZn material, wherein the raw materials of the low-temperature sintered high magnetic permeability and high Curie temperature NiCuZn material are composed of a main component and a secondary component; the raw materials of the main component are composed of 49.0-54 mol% Fe2O3, 22.5-36.5 mol% ZnO, 12.5-19.0 mol% NiO and 2.0-4.5 mol% CuO; the raw materials of the secondary component include V2O5, MoO3, ZrO2 and WO3, wherein the content of V2O5 is 0.01-0.2wt% of the mass of the main component, the content of MoO3 is 0.01-0.2wt% of the mass of the main component, the content of ZrO2 is 0.01-0.05wt% of the mass of the main component, and the content of WO3 is 0.01-0.05wt% of the mass of the main component.
[0005] In the present application, the total molar amount of the NiCuZn ferrite material is 100%, and the molar percentage of Fe2O3 is 49.0-54.0 mol%, such as 49 mol%, 49.4 mol%, 50.4 mol%, 51.6 mol%, 52.8 mol% or 54 mol%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable; ZnO, NiO and CuO are also applicable;
[0006] Preferably, the raw materials of the main component are composed of 49.0-51.5 mol% Fe2O3, 30.5-36.5 mol% ZnO, 12.5-15.0 mol% NiO and 2.0-3.0 mol% CuO. As a preferred technical scheme of the present invention, but not as a limitation to the technical scheme provided by the present invention, the technical objectives and beneficial effects of the present invention can be better achieved and realized through the following preferred technical scheme.
[0007] By adopting the above technical solution, the content of ZnO is controlled within a reasonable range in the present application, because in NiZnCu ferrite, high magnetic permeability requires an increase in the ZnO content. 2+ As the content increases, it will replace the Fe 3+ When the ions are squeezed to the B position, the molecular magnetic moment in the material will increase, which will lead to an increase in magnetic permeability. However, the working temperature of the material will change at the same time. 2+ As the ferrite contains more zinc ions, the number of magnetic ions at the A and B positions decreases, the super exchange interaction between the A and B positions weakens, and the Curie temperature T c It will drop significantly, and the application scope and application value of the ferrite material produced will be greatly reduced. In particular, it cannot be used in mobile terminal devices, and the value of the material will be greatly reduced.
[0008] Optionally, the auxiliary component raw materials include V2O5, MoO3, ZrO2 and WO3, the V2O5 content is 0.01-0.2wt% of the main component mass, the MoO3 content is 0.01-0.2wt% of the main component mass, the ZrO2 content is 0.01-0.05wt% of the main component mass, the WO3 content is 0.01-0.05wt% of the main component mass, and the mass percentage of V2O5 based on the standard is 0.01-0.2wt%, for example, 0.01wt%, 0.05wt%, 0.10wt%, 0.14wt% or 0.2wt%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable, and the same applies to the mass percentages of MoO3, WO3 and ZrO2.
[0009] Preferably, the V2O5 content is 0.09-0.2wt% of the main component mass, the MoO3 content is 0.12-0.2wt% of the main component mass, the ZrO2 content is 0.04wt% of the main component mass, and the WO3 content is 0.02wt% of the main component mass.
[0010] Optionally, the auxiliary component raw materials also include Y2O3 and Li2CO3, the content of Y2O3 is 0.01-0.1wt% of the mass of the main component, and the content of Li2CO3 is 0.01-0.2wt% of the mass of the main component.
[0011] Preferably, the auxiliary component raw material also includes Y2O3 and Li2CO3, the content of Y2O3 is 0.01-0.1wt% of the mass of the main component, and the content of Li2CO3 is 0.12-0.2wt% of the mass of the main component.
[0012] By adopting the above technical scheme, V2O5, MoO3, ZrO2, WO3 and Y2O3, Li2CO3 in the auxiliary raw materials are compounded, the growth of grains can be better controlled during the sintering process, the density and uniformity of NiZnCu ferrite can be improved, and the sintering temperature can be further reduced, thereby improving the electromagnetic properties of the prepared NiZnCu ferrite material.
[0013] The auxiliary raw materials V2O5, MoO3, ZrO2, WO3, Y2O3 and Li2CO3 in this application have the effect of promoting material densification, promoting grain growth, improving the initial magnetic permeability of the material, and reducing the sintering temperature to a certain extent, but they should not be excessive. The auxiliary raw materials are mostly non-magnetic substances, which will weaken the super exchange between the A and B positions of the NiZnCu ferrite, resulting in a decrease in the Curie temperature Tc and the saturation magnetic induction intensity Bs of the material. Due to the extremely low content of the auxiliary raw materials, they are not included in the total molar amount or total mass of the NiCuZn ferrite material in the calculation, but the total mass of Fe2O3, ZnO, NiO and CuO is directly used as the standard for measuring the amount of each component added in the auxiliary raw materials.
[0014] Optionally, the density of the low temperature sintered high magnetic permeability and high Curie temperature NiCuZn material is 5.1-5.35 g / cm 3 .
[0015] Preferably, the density of the low temperature sintered high magnetic permeability and high Curie temperature NiCuZn material is 5.15-5.25 g / cm 3 .
[0016] In a second aspect, the present application provides a method for preparing the above-mentioned low temperature sintered high magnetic permeability and high Curie temperature NiCuZn material, comprising the following steps:
[0017] S1 selects the main component raw materials and mixes the ingredients according to the proportion;
[0018] S2, ball milling the main component raw material of step S1, and spray granulating it to obtain a mixed material;
[0019] S3, pre-calcining the mixed material obtained in step S2, heating the mixture to 780-860°C at a heating rate of 1-3°C / min, keeping the temperature for 2-3h, and cooling to obtain a pre-calcined material;
[0020] S4, crushing the pre-burned material, adding auxiliary raw materials, performing secondary ball milling, and performing secondary spray granulation to obtain granulated material; S5, dry pressing the granulated material obtained in step S4, with a molding pressure of 6-8Mpa, to obtain a ring-shaped embryo;
[0021] S6. Sinter the annular embryo obtained in step S5, heat it to 150°C at a heating rate of 1.0-2.0°C / min, heat it to 500°C at a heating rate of 0.5-1.0°C / min, and then heat it to 980-1100°C at a heating rate of 1.2-2.0°C / min, keep it warm for 2-4 hours, and cool it to obtain a low-temperature sintered high magnetic permeability and high Curie temperature NiCuZn material.
[0022] Optionally, in step S2, the weight ratio of the raw material, deionized water and steel ball during the ball milling process is 2:1:6, and PVA is added to the raw material at the same time, the amount of PVA is 0.5-0.8wt% of the raw material, the ball mill speed is 180-230r / min, and the ball milling time is 1-2h. The PVA added during ball milling is PVA dissolved in water to form a PVA glue, which is then added to the ball mill. The mass fraction of the PVA glue is about 8-15wt%, and the amount of PVA is the amount of dry glue before PVA forms a glue. Similar expressions below apply the same.
[0023] Optionally, in step S4, the weight ratio of the raw material, deionized water and steel balls during the secondary ball milling process is 2:1:6, and PVA is added to the raw material at the same time, the amount of PVA is 1-1.5wt% of the raw material, the ball mill speed is 220-280r / min, and the ball milling time is 2-3h.
[0024] Preferably, the size of the steel ball is φ5-12 mm.
[0025] Optionally, in step S2, the particle size D50 of the raw material after the first ball milling is 4-6 μm.
[0026] Optionally, in step S4, the particle size D50 of the raw material after secondary ball milling is 0.5-4 μm.
[0027] Optionally, in step S4, the raw material after the secondary ball milling is transferred to a storage tank, and a defoamer and a dispersant are added to obtain a slurry, which is stirred for 1-2 hours and then spray granulated, wherein the amount of the defoamer added is 1-2 ml / kg, and the amount of the dispersant added is 0.8-1.5 ml / kg.
[0028] Optionally, in step S4, during the spray granulation process, the spray inlet temperature is controlled at 250-270°C, and the outlet temperature is controlled at 80-110°C.
[0029] Optionally, the particle size of the granulated material prepared in step S4 is 100-250 mesh, and the bulk weight of the granulated material is 1.28-1.4 g / cm3.
[0030] Optionally, the moisture content of the granulated material prepared in step S4 is 0.15-0.35wt%.
[0031] Preferably, in step S6, the annular embryo obtained in step S5 is sintered, the temperature is increased to 150°C at a heating rate of 1.0-2.0°C / min, the temperature is increased to 500°C at a heating rate of 0.5-1.0°C / min, the system is pressurized by 1-1.4t, and the temperature is increased to 980-1050°C at a heating rate of 1.2-2.0°C / min, kept warm for 2-3h, and cooled to obtain a low-temperature sintered high magnetic permeability and high Curie temperature NiCuZn material.
[0032] By adopting the above technical scheme and the hot pressing sintering method, the sintering temperature of hot pressing sintering is lower than that of ordinary sintering. The sintering temperature of ordinary sintering needs to reach 1050-1100°C and the time is 3-4h, while the sintering temperature of hot pressing sintering is 980-1050°C and the sintering time is 2-3h. The sintering time of hot pressing sintering is shorter, the overall energy consumption is less, the prepared NiCuZn material is denser and more uniform, and the grown grains are smaller. The electromagnetic properties of the prepared NiCuZn material are better, and the sintering time is greatly shortened, the energy consumption cost is lower, and it is more environmentally friendly.
[0033] In summary, the present invention includes at least one of the following beneficial technical effects:
[0034] 1. The high permeability and high Curie temperature NiCuZn soft ferrite material prepared in the present application not only has high initial permeability and high Curie temperature, but also has higher saturation magnetic flux density and high surface resistance. The present invention can realize the requirements of miniaturization and high operating temperature for magnetic materials.
[0035] 2. The preparation method of the present application has a short process, is easy to control, has good product stability, and is conducive to mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is an electron microscope image of a cross-section of a magnetic ring of the NiCuZn soft ferrite material obtained in Example 2;
[0037] Figure 2 This is an electron microscope image of a cross-section of a magnetic ring of a NiCuZn soft ferrite material prepared in Comparative Example 4;
[0038] Figure 3 This is an electron microscope image of the magnetic ring surface of the NiCuZn soft ferrite material prepared in Example 11;
[0039] Figure 4 This is an electron microscope image of the magnetic ring surface of the NiCuZn soft ferrite material prepared in Example 16. DETAILED DESCRIPTION
[0040] The present application is further described in detail below with reference to the embodiments.
[0041] The present application designs a low-temperature sintered high magnetic permeability and high Curie temperature NiCuZn material, wherein the raw materials of the low-temperature sintered high magnetic permeability and high Curie temperature NiCuZn material are composed of a main component and a secondary component;
[0042] The raw materials of the main component are composed of 49.0-54mol% Fe2O3, 22.5-36.5mol% ZnO, 12.5-19.0mol% NiO and 2.0-4.5mol% CuO; the raw materials of the secondary components include V2O5, MoO3, ZrO2 and WO3, among which the content of V2O5 is 0.01-0.2wt% of the mass of the main component, the content of MoO3 is 0.01-0.2wt% of the mass of the main component, the content of ZrO2 is 0.01-0.05wt% of the mass of the main component, and the content of WO3 is 0.01-0.05wt% of the mass of the main component.
[0043] The low temperature sintered high magnetic permeability and high Curie temperature NiCuZn material of the present application is prepared by the following method, including the following steps:
[0044] S1. Select the main ingredients and mix them according to the proportion;
[0045] S2, ball milling the main component raw material of step S1, and spray granulating it to obtain a mixed material;
[0046] S3, pre-calcining the mixed material obtained in step S2, heating the mixture to 780-860°C at a heating rate of 1-3°C / min, keeping the temperature for 2-3h, and naturally cooling the mixture to room temperature to obtain a pre-calcined material;
[0047] S4, crushing the pre-burned material, adding auxiliary raw materials, performing secondary ball milling, and performing secondary spray granulation to obtain granulated material; S5, dry pressing the granulated material obtained in step S4, with a molding pressure of 6-8Mpa, to obtain a ring-shaped embryo;
[0048] S6. Sinter the annular embryo obtained in step S5, heat it to 150°C at a heating rate of 1.0-2.0°C / min, heat it to 500°C at a heating rate of 0.5-1.0°C / min, and then heat it to 980-1100°C at a heating rate of 1.2-2.0°C / min, keep it warm for 2-4 hours, and cool it to obtain a low-temperature sintered high magnetic permeability and high Curie temperature NiCuZn material.
[0049] The technical problem solved by the present application is that some of the existing public technical documents and patent documents have low initial magnetic permeability, some have low Curie temperature, and some have low saturation magnetic flux density. It is difficult to achieve high initial magnetic permeability, high Curie temperature and high saturation magnetic flux density at the same time. Therefore, it is impossible to meet the use requirements of soft magnetic materials for miniature high-quality inductors, pulse transformers, electromagnetic interference suppressors, etc., and it does not meet the development trend of miniaturization, high power and wide temperature of electronic products. The high magnetic permeability and high Curie temperature NiCuZn soft magnetic ferrite material prepared in the present application not only has high initial magnetic permeability and high Curie temperature, but also has higher saturation magnetic flux density and high surface resistance. The present invention can realize the requirements of miniaturization and high operating temperature for magnetic materials.
[0050] Examples 1-7
[0051] Examples 1-7 are low-temperature sintered high magnetic permeability and high Curie temperature NiCuZn materials made with different raw material ratios. The specific raw material ratios are shown in Table 1.
[0052] Table 1
[0053]
[0054]
[0055] The preparation process of the NiCuZn material in Examples 1-7 is as follows:
[0056] S1. Select the main ingredients and mix them according to the proportion;
[0057] S2. The main component raw material of step S1 is ball-milled once and spray-granulated once to obtain a mixed material; during the ball-milling process, the weight ratio of the raw material, deionized water and steel balls is 2:1:6, and PVA is added to the raw material at the same time, the amount of PVA is 0.6wt% of the raw material, the ball mill speed is 200r / min, and the ball milling time is 1.5h; the particle size D50 of the raw material after the ball milling is 5μm.
[0058] S3, pre-calcining the mixed material obtained in step S2, heating the mixture to 850°C at a heating rate of 1.2°C / min, keeping the temperature for 2.5h, and naturally cooling the mixture to room temperature to obtain a pre-calcined material;
[0059] S4. The pre-sintered material is crushed, and auxiliary raw materials are added for secondary ball milling. During the secondary ball milling, the weight ratio of the raw materials, deionized water and steel balls is 2:1:6. PVA is added to the raw materials at the same time. The amount of PVA is 1.3wt% of the raw materials. The ball mill speed is 260r / min, and the ball milling time is 2.5h. The particle size D50 of the raw materials after the secondary ball milling is 1.2μm.
[0060] After that, the raw materials after the secondary ball milling were transferred to the storage tank, and the slurry was obtained by adding the defoamer and dispersant. After stirring for 1 hour, spray granulation was performed, wherein the amount of defoamer added was 2ml / kg, and the amount of dispersant added was 1ml / kg. During the spray granulation process, the spray inlet temperature was controlled at 265℃, and the outlet temperature was controlled at 100℃. Finally, the granulated material was obtained, the particle size of the granulated material was 150 mesh, and the bulk weight of the granulated material was 1.35g / cm 3 , the moisture content of the granulated material is 0.3wt%.
[0061] S5. The granulated material obtained in step S4 is dry pressed at a molding pressure of 7.5 MPa to obtain an annular embryo body having a specification of φ25 mm×φ15 mm×10 mm.
[0062] S6. Heat the annular embryo obtained in step S5 to 150°C at a heating rate of 1.5°C / min, heat it to 500°C at a heating rate of 0.6°C / min, and then heat it to 1080°C at a heating rate of 1.8°C / min, keep it warm for 3.5 hours, and cool it naturally to obtain a low-temperature sintered high magnetic permeability and high Curie temperature NiCuZn material.
[0063] In Examples 1-7, the defoamer used is BYK-024 silicone defoamer.
[0064] The dispersant used in Examples 1-7 was polycarboxylic acid amine salt dispersant 5029 (Weifang Dadong Chemical Co., Ltd.).
[0065] Embodiment 8-11
[0066] Example 8 is based on Example 2, with the difference being that the auxiliary component raw material in Example 8 also includes Y2O3, wherein the amount of Y2O3 used is 0.06wt% of the mass of the main component.
[0067] Example 9 is based on Example 2, with the difference that the auxiliary component raw material in Example 9 also includes Li2CO3, wherein the amount of Li2CO3 is 0.15wt% of the mass of the main component.
[0068] Example 10 is based on Example 2, with the difference being that the auxiliary raw materials in Example 10 also include Y2O3 and Li2CO3, wherein the amount of Y2O3 is 0.06wt% of the mass of the main component, and the amount of Li2CO3 is 0.08wt% of the mass of the main component.
[0069] Example 11 is based on Example 2, with the difference that the auxiliary component raw materials in Example 11 also include Y2O3 and Li2CO3, wherein the amount of Y2O3 is 0.06wt% of the mass of the main component, and the amount of Li2CO3 is 0.15wt% of the mass of the main component.
[0070] Examples 12-13
[0071] Example 12 is based on Example 11, with the difference that in Example 12, the particle size D50 of the raw material after secondary ball milling in step S4 is 0.5 um.
[0072] Example 13 is based on Example 11, with the difference that in Example 13, the particle size D50 of the raw material after secondary ball milling in step S4 is 4 um.
[0073] Examples 14-15
[0074] Example 14 is based on Example 11, except that in Example 14, the water content of the granulated material prepared in step S4 is 0.15wt%.
[0075] Example 15 is based on Example 11, with the difference that in Example 15, the water content of the granulated material prepared in step S4 is 0.35wt%.
[0076] Examples 16-17
[0077] Example 16 is based on Example 11, with the difference that: in Example 16, hot pressing sintering is adopted in the final sintering stage, that is, step S6 in Example 16 is: heating the annular embryo obtained in step S5 to 150°C at a heating rate of 1.5°C / min, heating to 500°C at a heating rate of 0.6°C / min, pressurizing the system by 1.3t, and heating to 980°C at a heating rate of 1.8°C / min, keeping warm for 2.6h, and cooling naturally to obtain low-temperature sintered high magnetic permeability and high Curie temperature NiCuZn material.
[0078] Example 17 is based on Example 11, with the difference that: in the preparation process of Example 17, step S6 is changed to: heating the annular embryo obtained in step S5 to 150°C at a heating rate of 1.5°C / min, heating to 500°C at a heating rate of 0.6°C / min, and then heating to 980°C at a heating rate of 1.8°C / min, keeping warm for 3.5 hours, and cooling naturally to obtain a low-temperature sintered high magnetic permeability and high Curie temperature NiCuZn material.
[0079] Comparative Examples 1-5
[0080] Comparative Example 1 is based on Example 2, except that the ratio of the main component raw materials in Comparative Example 1 is changed to 57 mol% Fe2O3, 33 mol% ZnO, 14.5 mol% NiO and 12.5 mol% CuO.
[0081] Comparative Example 2 is based on Example 2, except that the ratio of the main component raw materials in Comparative Example 2 is changed to 51 mol% Fe2O3, 19 mol% ZnO, 14.5 mol% NiO and 12.5 mol% CuO.
[0082] Comparative Example 3 is based on Example 2, except that the auxiliary component raw material in Comparative Example 3 does not contain ZrO2.
[0083] Comparative Example 4 is based on Example 2, except that the auxiliary component raw material in Comparative Example 4 does not contain WO3.
[0084] Comparative Example 5 is based on Example 2, except that WO3 in the auxiliary component raw material in Comparative Example 5 is replaced by the same amount of Bi2O3.
[0085] Performance Testing
[0086] The sample rings of NiCuZn materials prepared in Examples 1-17 and Comparative Examples 1-5 were tested on an HP4284A impedance analyzer to measure the initial magnetic permeability of the sample ring at 1 MHz and the saturation magnetic flux density at room temperature; the density of the sample ring was measured by the buoyancy method; the change curve of the magnetic permeability μ and the temperature T was tested by an inductance tester to infer the Curie temperature T c The measurement results are shown in Table 2.
[0087] Table 2
[0088]
[0089]
[0090] By analyzing the data in Table 2 and comparing Examples 1-17, when the main components of the raw materials of the NiCuZn material contain 49.0-51.5mol% Fe2O3, 30.5-36.5mol% ZnO, 12.5-15.0mol% NiO and 2.0-3.0mol% CuO, and the content of V2O5 in the auxiliary components is 0.12wt% of the main component mass, the content of MoO3 is 0.14wt% of the main component mass, the content of ZrO2 is 0.04wt% of the main component mass, the content of WO3 is 0.02wt% of the main component mass, the content of Y2O3 is 0.06wt% of the main component mass, and the content of Li2CO3 is 0.15wt% of the main component mass, the density of the obtained NiCuZn material is 5.1-5.5g / cm 3 The initial magnetic permeability at 1MHz reaches more than 2300, and the Curie temperature can reach 147°C. It also has a saturation magnetic flux density close to 360mT and good electromagnetic properties. The NiCuZn ferrite material prepared in this application not only has high initial magnetic permeability and high Curie temperature, but also has higher saturation magnetic flux density and high surface resistance. This application can meet the requirements of miniaturized and high operating temperature devices for magnetic materials.
[0091] Will Figure 1 and Figure 2 By comparison, it can be found that the grains in the cross-section electron microscope image of the magnetic ring of Example 2 are smaller and the structure is denser.
[0092] Will Figure 3 and Figure 4 By comparison, it can be found that the surface density of the magnetic ring prepared by hot pressing sintering in Example 16 is better. After testing its mechanical properties, the strength and toughness of the magnetic ring prepared in Example 16 are better than those in Example 11.
[0093] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A low temperature sintered high magnetic permeability high Curie temperature NiCuZn material, characterized in that: The raw materials of the low-temperature sintered high-magnetic permeability and high-Curie temperature NiCuZn material are composed of a main component raw material and a secondary component raw material; The main raw material consists of 51-54 mol% Fe2O3, 22.5-36.5 mol% ZnO, 12.5-19.0 mol% NiO and 2.0-4.5 mol% CuO, and the sum of the molar percentages of the main raw materials is 100%; The auxiliary component raw materials include V2O5, MoO3, ZrO2 and WO3, wherein the content of V2O5 is 0.2 wt% of the main component, the content of MoO3 is 0.01-0.2 wt% of the main component, the content of ZrO2 is 0.01-0.05 wt% of the main component, and the content of WO3 is 0.01-0.05 wt% of the main component; The method for preparing the low temperature sintered high magnetic permeability and high Curie temperature NiCuZn material comprises the following steps: S1. Select the main ingredients and mix them according to the proportion; S2, ball milling the main component raw material of step S1, and spray granulating it to obtain a mixed material; S3, pre-calcining the mixed material obtained in step S2, heating the mixture to 780-860°C at a heating rate of 1-3°C / min, keeping the temperature for 2-3h, and cooling to obtain a pre-calcined material; S4, crushing the pre-burned material, adding auxiliary raw materials, performing secondary ball milling, and performing secondary spray granulation to obtain granulated material; S5, dry-pressing the granulated material obtained in step S4 at a pressure of 6-8 MPa to obtain a ring-shaped embryo; S6, sintering the annular embryo obtained in step S5, heating the temperature to 150°C at a heating rate of 1.0-2.0°C / min, heating the temperature to 500°C at a heating rate of 0.5-1.0°C / min, and then heating the temperature to 980-1100°C at a heating rate of 1.2-2.0°C / min, keeping the temperature for 2-4 hours, and cooling to obtain a low-temperature sintered high magnetic permeability and high Curie temperature NiCuZn material; Alternatively, in step S6, the annular embryo obtained in step S5 is sintered, the temperature is increased to 150°C at a heating rate of 1.0-2.0°C / min, the temperature is increased to 500°C at a heating rate of 0.5-1.0°C / min, the system is pressurized by 1-1.4t, and the temperature is increased to 980-1050°C at a heating rate of 1.2-2.0°C / min, kept warm for 2-3h, and cooled to obtain a low-temperature sintered high magnetic permeability and high Curie temperature NiCuZn material.
2. The low temperature sintered high magnetic permeability and high Curie temperature NiCuZn material according to claim 1, characterized in that: The auxiliary component raw materials also include Y2O3 and Li2CO3, wherein the content of Y2O3 is 0.01-0.1wt% of the mass of the main component, and the content of Li2CO3 is 0.01-0.2wt% of the mass of the main component.
3. The low temperature sintered high magnetic permeability high Curie temperature NiCuZn material according to claim 1, characterized in that: The density of the low-temperature sintered high-permeability and high-Curie temperature NiCuZn material is 5.1-5.35 g / cm 3 .
4. A method for preparing the low temperature sintered high magnetic permeability and high Curie temperature NiCuZn material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Select the main ingredients and mix them according to the proportion; S2, ball milling the main component raw material of step S1, and spray granulating it to obtain a mixed material; S3, pre-calcining the mixed material obtained in step S2, heating the mixture to 780-860°C at a heating rate of 1-3°C / min, keeping the temperature for 2-3h, and cooling to obtain a pre-calcined material; S4, crushing the pre-burned material, adding auxiliary raw materials, performing secondary ball milling, and performing secondary spray granulation to obtain granulated material; S5, dry-pressing the granulated material obtained in step S4 at a pressure of 6-8 MPa to obtain a ring-shaped embryo; S6. Sinter the annular embryo obtained in step S5, heat it to 150°C at a heating rate of 1.0-2.0°C / min, heat it to 500°C at a heating rate of 0.5-1.0°C / min, and then heat it to 980-1100°C at a heating rate of 1.2-2.0°C / min, keep it warm for 2-4 hours, and cool it to obtain a low-temperature sintered high magnetic permeability and high Curie temperature NiCuZn material.
5. The method for preparing the low temperature sintered high magnetic permeability and high Curie temperature NiCuZn material according to claim 4, characterized in that: In the step S2, the weight ratio of the raw material, deionized water and steel balls during the primary ball milling process is 2:1:6, and PVA is added to the raw material at the same time, the amount of PVA is 0.5-0.8wt% of the raw material, the ball mill speed is 180-230r / min, and the ball milling time is 1-2h; in the step S4, the weight ratio of the raw material, deionized water and steel balls during the secondary ball milling process is 2:1:6, and PVA is added to the raw material at the same time, the amount of PVA is 1-1.5wt% of the raw material, the ball mill speed is 220-280r / min, and the ball milling time is 2-3h.
6. The method for preparing the low temperature sintered high magnetic permeability and high Curie temperature NiCuZn material according to claim 4, characterized in that: In the step S2, the particle size D50 of the raw material after the first ball milling is 4-6 μm; in the step S4, the particle size D50 of the raw material after the second ball milling is 0.5-4 μm.
7. The method for preparing the low temperature sintered high magnetic permeability and high Curie temperature NiCuZn material according to claim 4, characterized in that: The particle size of the granulated material obtained in step S4 is 100-250 mesh, and the bulk weight of the granulated material is 1.28-1.4 g / cm 3 .
8. The method for preparing the low temperature sintered high magnetic permeability and high Curie temperature NiCuZn material according to claim 4, characterized in that: The moisture content of the granulated material obtained in step S4 is 0.15-0.35wt%.
9. The method for preparing the low temperature sintered high magnetic permeability and high Curie temperature NiCuZn material according to claim 4, characterized in that: In the step S6, the annular embryo body obtained in step S5 is sintered, the temperature is increased to 150°C at a heating rate of 1.0-2.0°C / min, the temperature is increased to 500°C at a heating rate of 0.5-1.0°C / min, the system is pressurized by 1-1.4t, and the temperature is increased to 980-1050°C at a heating rate of 1.2-2.0°C / min, and the temperature is kept for 2-3h, and cooled to obtain a low-temperature sintered high magnetic permeability and high Curie temperature NiCuZn material.
Citation Information
Patent Citations
Soft magnetic material and preparation method thereof
CN104230324A
Nickel-zinc-copper ferrite material suitable for wide-temperature loading and preparation method of nickel-zinc-copper ferrite material
CN115417664A
Low loss ni-zn based ferrite
JP2003300774A